Optimizing Learner Management In Early Chilhood Education - Qurrotul Ain, Azwa; Nuraulia Azmi, Nailah; Az-Zaily, Nayla; Suhardi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
This study aims to examine and describe the importance of optimizing student management in early childhood education (ECE) as an approach to improving the quality of education programs. Student management is an important element that plays a role in supporting the overall growth of children, including cognitive, social, emotional, motoric, and spiritual dimensions. This study applies a descriptive qualitative approach with a literature review method (library research), relying on primary and secondary data from various reliable sources to build a theoretical basis and conceptual framework.The results of the study indicate that optimal student management is determined by the principles, objectives, functions, and scope that are implemented professionally and in an integrated manner. In addition, cooperation between teachers, parents, and the community plays a major role in creating a positive and inclusive learning atmosphere. The active involvement of all parties, as reflected in the implementation of the Pancasila Student Profile Strengthening Project (P5), strengthens the synergy between home and school. Supporting factors such as the active role of teachers and structured activity planning contribute to the success of student management. However, there are still challenges such as limited facilities, low enthusiasm for learning, and minimal parental participation. Therefore, an adaptive, collaborative organizational approach is needed, and is able to appreciate the uniqueness of each child. Thus, strengthening the management of learners in Early Childhood Education (ECE) is a strategic step in creating an efficient, sustainable, and holistically child-growth-oriented learning system.